Economic dispatch using artificial immune system / Noraliza Sidek - Sidek, Noraliza (2006)
This project presents an Artificial Immune System based approach to solve economic dispatch problem in a power system. The Artificial Immune System developed in the project was tested on two objective functions for optimizing the economic dispatch problem that are the total generation cost and the incremental cost function. The performances of the two objective functions were compared in term of minimizing the total cost of generation in satisfying the load demand together with the transmission losses. The effectiveness of this technique was tested on the IEEE 26-bus system and analysis of results is presented.